2017
DOI: 10.3348/kjr.2017.18.6.881
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Novel Intracycle Motion Correction Algorithm on Dual-Energy Spectral Coronary CT Angiography: A Study with Pulsating Coronary Artery Phantom at High Heart Rates

Abstract: ObjectiveUsing a pulsating coronary artery phantom at high heart rate settings, we investigated the efficacy of a motion correction algorithm (MCA) to improve the image quality in dual-energy spectral coronary CT angiography (CCTA).Materials and MethodsCoronary flow phantoms were scanned at heart rates of 60–100 beats/min at 10-beats/min increments, using dual-energy spectral CT mode. Virtual monochromatic images were reconstructed from 50 to 90 keV at 10-keV increments. Two blinded observers assessed image qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Excessively low CT value will weaken the contrast between the blood vessel and surrounding tissue, and the coronary artery can be displayed clearly-when the CT value is approximately 350 HU. Our previous study also found that the adequate enhancement obtained at the lower monochromatic energy levels in the dual-energy spectral CT imaging (50 keV, 60 keV, 70 keV) was also important for a motion correction algorithm that requires the real-time tracking of coronary artery motion to be successful 17 . On the other hand, excessively high CT values in the vessel could also be detrimental.…”
Section: Discussionmentioning
confidence: 91%
“…Excessively low CT value will weaken the contrast between the blood vessel and surrounding tissue, and the coronary artery can be displayed clearly-when the CT value is approximately 350 HU. Our previous study also found that the adequate enhancement obtained at the lower monochromatic energy levels in the dual-energy spectral CT imaging (50 keV, 60 keV, 70 keV) was also important for a motion correction algorithm that requires the real-time tracking of coronary artery motion to be successful 17 . On the other hand, excessively high CT values in the vessel could also be detrimental.…”
Section: Discussionmentioning
confidence: 91%
“…Cho et al (8) demonstrated that the coronary artery image quality and diagnostic accuracy (i.e., measurement errors of the MLA and MLD) improved on using MCA at high HRs (i.e., 80 bpm and 100 bpm), although there was no benefit at low HRs (i.e., 60 bpm). Xing et al (17) also showed that the coronary artery image quality improved on using MCA at 70–100 bpm (10-bpm interval) on monochromatic levels of 50, 60, and 70 keV in their phantom study using dual-energy spectral CT. Their results have similar trends to our results. However, they used a 64-slice single-source dual-energy CT scanner, and their maximum HR was set at 100 bpm.…”
Section: Discussionmentioning
confidence: 97%
“…Prior studies have documented beneficial effects of MCA in terms of image quality and diagnostic accuracy using a pulsating coronary phantom (Mocomo; Fuyo Corp, Tokyo, Japan) (817). Cho et al (8) demonstrated that the coronary artery image quality and diagnostic accuracy (i.e., measurement errors of the MLA and MLD) improved on using MCA at high HRs (i.e., 80 bpm and 100 bpm), although there was no benefit at low HRs (i.e., 60 bpm).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the evaluation of the hepatic vascular system is primarily through the use of multi-slice computed tomography (CT) angiography (MSCTA). Recently, spectral CT imaging has been gradually applied clinically ( 5 6 7 ). Spectral CT energy imaging using single-source instantaneous kVp switching technology can switch between high and low tube voltage (140 kVp and 80 kVp) instantaneously in less than 0.5 ms for a quasi-simultaneous sampling of two sets of data.…”
Section: Introductionmentioning
confidence: 99%